Analysis Of Employee's Satisfaction Sub-District Office In The South Nias Regency - Timotius Duha (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2019)
This study aims to seek the influence of independent variables on the dependent variable through an intermediate variable. Analyzing data through path analysis using Partial Least Square (PLS) with single-mediator. Processing data using Warp PLS 5.0 software. Respondents of this study were employees at the Sub-District Office (Maniamolo, Amandraya, O’ou) who were neighbors and were in the South Nias Regency, around 61 people. The result of the study showed that the Partners' Support has a positive effect on discipline because coworkers are a source of inspiration for employees to learn, imitate their coworkers for discipline. The support of coworkers has a positive effect on job satisfaction because coworkers are able to make employees comfortable, at home and love their jobs. Discipline has a positive effect on job satisfaction because employees' efforts to become disciplines are supported by their colleagues. The support of coworkers has a positive effect on job satisfaction mediated by discipline because a colleague who applies discipline will encourage other employees to be disciplined. Hence, all employees are able to be disciplined, employees will have job satisfaction.